Don't look only to Brussels to increase the supply of safe assets in the European Union - Francesco Papadia; Heliodoro Temprano Arroyo (Bruegel, 2022)
A sufficient supply of safe assets denominated in euros is critical if the European Union is to achieve full banking and capital markets union while fostering the euro's international role. The European debate on developing the supply of safe assets has so far focused on the possible creation of a common safe asset. This has tended to underplay the potential contribution of sovereign assets. Expanding the supply of national safe assets, notably through the gradual implementation of fiscal and growth-oriented structural policies in euro-area countries, leading to upgrading of their sovereign ratings, provides a promising, and perhaps more feasible, option. An upgrade to triple A of those euro-area countries that are currently rated double A could produce substantially more safe assets than most common safe asset proposals, including those based on the development of 'synthetic' safe assets. There has been a remarkable increase in the share of supranational assets in the stock of euro-based safe assets since 2008, reflecting downgrades in sovereign ratings and the EU's financial responses to the euro-area crisis and the pandemic. However, safe assets in euro remain dominated by those issued by euro-area governments. Although common safe assets have certain advantages over national safe assets, reflecting their built-in risk diversification properties, there is currently not much political appetite for such proposals. Meanwhile, sovereign safe assets already offer many of the advantages of common safe assets. Sound fiscal policies and growth-stimulating reforms, which are in any case desirable, should be implemented to improve the credit ratings of euro-area sovereigns. This might not be politically feasible in the short-term, given the difficult economic environment currently faced by the EU, but it should be a key component of the EU's medium-term safe asset strategy. Should the political consensus be found to create a common safe asset, such an asset could be incorporated into the euro area's existing safe asset system, reinforcing its positive effects.
Keywords: 330